Fiqh of International Relations in the Era of Nation State in the Perspective of the Council of Indonesian Ulama - Firdaus, Robitul; Muhyiddin (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2025)
This article aims to analyze the decision of the Indonesian Ulama Council concerning the principles of international relations stipulated in the 8th Ijtima' Ulama forum in 2024. The study has three primary focuses: to scrutinize the socio-political context as the background of the MUI's decision, to examine its arguments and methodology, and to investigate the social responses to the MUI's decision. A descriptive analytical approach is used to describe and understand a phenomenon that occurs, involving causes and effects. As the findings, the study reveals that the emergence of this MUI decision responded to the Palestine-Israel conflict escalation at the end of 2023, which caused diverse policies of Muslim countries in the world. Previously, the MUI also issued a fatwa on supporting the struggle of Palestine. To support its argument, the MUI cited a series of arguments which still generally apply the qauly or textual approach. These arguments are written without adequate explanation regarding their context from istidlal or instinbath approach. Apart from that, there are debates among the public regarding the idea of boycotting pro-Israel products. The government tends to be neutral concerning the boycott campaign, while it supports the essence of the fatwa and the MUI decision to support the struggle of Palestine. This result suggests that the MUI should improve its fatwa writing design to avoid misinterpretation. Likewise, the study might have practical implications for the government to deal with such MUI’s religious thoughts.